PENGARUH SERVANT LEADERSHIP TERHADAP KINERJA KARYAWAN DENGAN BURNOUT SEBAGAI VARIABEL INTERVENING PADA NINJA XPRESS TIMIKA - Farida Tetroman; Kartika Wulan Sari; Habel Taime (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the effect of servant leadership on employee performance with burnout as an intervening variable at Ninja Xpress Timika. The data collection techniques used to obtain data in this research were observation and questionnaire techniques. Data analysis in this research uses path analysis. From the results of the analysis that has been carried out, the research results show that servant leadership has a positive and significant effect on the performance of Ninja Xpress Timika employees. The results of the second research showed that servant leadership had a negative effect on burnout. The results of the third research showed that burnout had a negative effect on employee performance at Ninja Xpress Timika. The results of the fourth research showed that servant leadership had a positive effect on employee performance through burnout at Ninja Xpress Timika